Unveiling the dynamics of organizational politics and their consequences on job performance in Thai local administrations - Waiphot Kulachai (Cogent Social Sciences)
This study explores the impact of Perceived Organizational Politics on Job Satisfaction, Job Stress, Employee Engagement, and Job Performance, with a focus on the mediating roles of job satisfaction, stress, and engagement. Data were collected from 204 local administration officials in Suphan Buri, Thailand, and analyzed using Structural Equation Modeling through JAMOVI software. The findings reveal that perceived organizational politics negatively affects job satisfaction and positively influences job stress, indicating that workplace politics leads to lower satisfaction and higher stress levels. However, organizational politics does not directly affect employee engagement or job performance, suggesting that other factors mediate these relationships. The study highlights that job satisfaction positively influences employee engagement, and engagement significantly impacts job performance, demonstrating that satisfied and engaged employees perform better. Additionally, job satisfaction and employee engagement mediate the relationship between organizational politics and performance, while job stress does not play a significant mediating role. These results suggest that enhancing job satisfaction and employee engagement is crucial for mitigating the negative effects of organizational politics on performance, particularly in local government settings. The study recommends that local administrations focus on improving job satisfaction and engagement to enhance employee performance and reduce the adverse impacts of workplace politics.